2018
DOI: 10.1097/md.0000000000013082
|View full text |Cite
|
Sign up to set email alerts
|

Immediate versus conventional postoperative tracheal extubation for enhanced recovery after liver transplantation

Abstract: Introduction:To systematically compare immediate postoperative tracheal extubation (IPTE) with conventional tracheal extubation (CTE) and to determine whether IPTE can achieve an enhanced recovery for adult patients underwent liver transplantation (LT) without additional risks. We designed a systematic review and meta-analysis.Methods:The RCTs, cohorts, case–controls, or case series that explored outcomes of IPTE after LT for adults were involved in our study. The Newcastle–Ottawa scale was used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
(58 reference statements)
0
12
0
2
Order By: Relevance
“…23 Prolonged mechanical ventilation may also increase right ventricular after load and even induce venous congestion of the liver graft, especially in those with pre-existing tricuspid regurgitation and raised pulmonary artery pressures (which is not uncommon in end-stage liver disease patients). 24 When comparing the reintubated group with the non-orotracheal reintubation (Retot) group, it can be observed that the ICU time values (14 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] days and 4 [5][6][7] days, < 0.001), mechanical ventilation time (6 [5-19] and 1 [1-3] days < 0.001) and mortality 57.9% vs. 19.1% were significantly higher in the reintubated group.…”
Section: Discussionmentioning
confidence: 99%
“…23 Prolonged mechanical ventilation may also increase right ventricular after load and even induce venous congestion of the liver graft, especially in those with pre-existing tricuspid regurgitation and raised pulmonary artery pressures (which is not uncommon in end-stage liver disease patients). 24 When comparing the reintubated group with the non-orotracheal reintubation (Retot) group, it can be observed that the ICU time values (14 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] days and 4 [5][6][7] days, < 0.001), mechanical ventilation time (6 [5-19] and 1 [1-3] days < 0.001) and mortality 57.9% vs. 19.1% were significantly higher in the reintubated group.…”
Section: Discussionmentioning
confidence: 99%
“…23 A ventilação mecânica prolongada também pode aumentar após carga no ventrículo direito e até mesmo induzir a congestão venosa do enxerto hepático, especialmente naqueles com insuficiência tricúspide preexistente e pressão arterial pulmonar elevada (o que não é incomum em pacientes com doença hepática terminal). 24 Ao comparar o grupo reintubado com o grupo reintubação Agostini APRA, Boin IFSF, Heidemann A, Tonella RM, Falcão ALE, Ratti LSR, Figueiredo LC, Martins LC não orotraqueal (Retot), observa-se que os valores de tempo de UTI (14 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] dias e 4 [5][6][7] dias, < 0,001), tempo de ventilação mecânica ( 6 [5-19] e 1 [1][2][3] dias < 0,001) e mortalidade 57,9% vs. 19,1% foram significativamente maiores no grupo reintubado.…”
Section: Discussionunclassified
“…Considering the high prevalence of multi-drug resistant bacteria in post-transplant patients induced by the excessive use of antibiotics(4), high speci city is especially necessary in clinical practice to avoid an unnecessary and overuse of antibiotics in low-risk patients. By contrast, all patients received peri-operative antibiotic therapy for 72 hr, and this has posed considerable challenge in predicting pneumonia at an early stage (23). Therefore, the novel XGBoost model as established in this study may assist clinicians in making optimal interventions and treatments, and eventually improve care for affected patients.…”
Section: Discussionmentioning
confidence: 99%